2015
DOI: 10.1007/s10853-015-8887-2
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution and mechanical properties of a submerged friction-stir-processed AZ91 magnesium alloy

Abstract: AZ91 casting alloy is subjected to friction stir processing (FSP) in air (NFSP) and under water (SFSP). The thermal histories of the two FSP procedures are measured, and their effects on microstructure evolution and mechanical properties of the experimental materials are investigated. Compared with NFSP, the peak temperature during SFSP is about 150°C lower and a much higher cooling rate of 13°C/s is gained. Both NFSP and SFSP produce uniform recrystallized microstructures with dominant high-angle grain bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Hofmann et al [ 8 ] prepared an Al-6061-T6 alloy with a grain size less than 200 nm by SFSP and supposed that SFSP could refine grains and improve the mechanical properties. Chai et al [ 20 ] produced an AZ91 alloy with an average grain size of 1.2 µm through SFSP, while the average grain size of NFSP sample was ~7.8 µm. During submerged friction stir processing, the shoulder of the tool makes firm contact with the materials after the pin inserted into the plates, and the process is finished in a few minutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hofmann et al [ 8 ] prepared an Al-6061-T6 alloy with a grain size less than 200 nm by SFSP and supposed that SFSP could refine grains and improve the mechanical properties. Chai et al [ 20 ] produced an AZ91 alloy with an average grain size of 1.2 µm through SFSP, while the average grain size of NFSP sample was ~7.8 µm. During submerged friction stir processing, the shoulder of the tool makes firm contact with the materials after the pin inserted into the plates, and the process is finished in a few minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the possibility of corrosion caused by water is limited. In addition, Chai et al [ 20 ] reported that the surfaces of the SFSP AZ91 alloy were relatively clean and no perceivable corrosion was mentioned in their paper. According to the anodic polarization curves in dilute electrolyte (0.001 N NaCl solution), the corrosion susceptibility of as-cast AZ61 magnesium alloy is similar to the as-cast AZ91 alloy [ 21 ], so SFSP can also be applied to the as-cast AZ61 magnesium alloy for microstructure refinement.…”
Section: Introductionmentioning
confidence: 99%
“…Since DRX takes place during FSP and significant grain refinement is achieved, according to classic Hall-Petch equation, the YS of FSP Mg–6Sn–2Zn samples should also be improved obviously. The combined enhancement of ductility and strength by FSP has been achieved in some Mg alloys [ 30 , 31 , 32 ]. However, there are also studies that have reported that FSP could only improve the ductility of Mg alloys.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated to be a simple, effective, and economical technique for grain refinement. Chai et al [28] reported that the average grain size of UFSP AZ91 was 1.2 µm, which was much finer than that of normal FSP conducted in the air (7.8 µm). Basil et al [29] also demonstrated that the average grain size of AZ31 attained were 18.9, 15.9, and 13.3 µm for FSP in air, submerged in hot water and submerged in cold water, respectively.…”
Section: Introductionmentioning
confidence: 95%